2012
DOI: 10.1159/000345979
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Extraction of Permanent Teeth in General Dental Practices in Tehran, Iran

Abstract: Objectives: The aim of this survey was to investigate the primary reason for extraction of permanent teeth, its correlations with age, gender and education level, as well as identify the important predictors for dental caries in general dental centers in Tehran, Iran. Subjects and Methods: The study was conducted over a period of 6 months; its population consisted of 1,382 patients, aged 9-95 years, who underwent tooth extraction. There were 673 (47.8%) male and 709 (51.3%) female patients. The frequency distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
87
4
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 28 publications
15
87
4
6
Order By: Relevance
“…This confirms the findings of the study in Family Health Units in Campina Grande, state of Pernambuco 29 , which showed caries and pain as the most reported reasons. However, these findings differ from studies with clinical insight, because they refer to conditions evaluated by professionals and not by individuals, being caries and periodontal disease the most prevalent reasons in these studies 1,7,30 . In the age group of young adults (20-44 years old), the other reasons variable appeared with high prevalence, and can be explained by the dental extractions performed with orthodontic indication.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This confirms the findings of the study in Family Health Units in Campina Grande, state of Pernambuco 29 , which showed caries and pain as the most reported reasons. However, these findings differ from studies with clinical insight, because they refer to conditions evaluated by professionals and not by individuals, being caries and periodontal disease the most prevalent reasons in these studies 1,7,30 . In the age group of young adults (20-44 years old), the other reasons variable appeared with high prevalence, and can be explained by the dental extractions performed with orthodontic indication.…”
Section: Discussionmentioning
confidence: 79%
“…This refers to the understanding that when the periodontal and restorative preventive procedures in primary care are not sought, there is progression of oral diseases and restriction of treatment 7,31 options. This data was also verified in the study with patients who donated the extracted teeth to a bank of human teeth of Curitiba, state of Paraná 32 , because most of those being interviewed claim to have searched for dental service only once before the decision of tooth extraction, i.e., the same day in which the procedure was carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the findings from the population we evaluated support this result. Thus, Jafarian and Etebarian (23) emphasized that periodontal disease-related tooth extraction was not observed in individuals younger than 20; rather, periodontal disease-related tooth extraction emerges as people age.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent teeth are extracted for various reasons such as dental caries, orthodontic reasons, periodontal disease, impacted teeth, failed dental treatments, pre-prosthetic considerations etc. [7]. Criterias which are taken into consideration before any extraction are tooth mobility, prosthetic planning ,severity of attachment loss, furcation involvement , endodontic-periodontal lesion, radiographic bone loss ( more than 50 % ) , grossly carious teeth [8].…”
Section: Discussionmentioning
confidence: 99%